RESPON SISWA TERHADAP PENGEMBANGAN MEDIA MODEL KEMAGNETAN BUMI - Muh. Husnul Fikri; Aris Doyan; Ahmad Harjono (Jurnal Penelitian Pendidikan IPA, 2015)
This study aims to develop instructional media materials science magnetism at the junior level Models Earth Magnetism (MKB)media. The study was conducted by using the approach of Research and Development by Borg & Gall modified by Sukmadinata into 3 stages: a preliminary study, test models and test the product. Modeling exercise carried out in two stages. Limited test phase conducted at SMK Islam Nurul Hikmah Langko West Lombok and wider scale trials as well as the testing phase at SMPN 3 Lingsar. Of wider scale pilot phase characteristics obtained MKB media. At the end of the pilot phase conducted a broader scale questionnaire to get students' response in the development of MKB media at 20 students. Students responded positively to the development of MKB media. Keywords : Media Model of Earth Magnetism , Student Response.